An antibody to isogeneic fibroblasts in the serum of diseased NZB mice - Liburd, E. (1974)
We have described a new autoantibody present in the serum of diseased NZB mice reactive with autochthonous and syngeneic fibroblasts. Allogeneic cells are not affected. This antibody can be specifically absorbed both by fibroblasts and lymphocytes from NZB but not from control mice. The antibody cannot act as a blocking factor to impair the cell-mediated killing of isogeneic fibroblasts by lymphocytes from diseased NZB mice. This suggests that the precise antigenic specificities of the cell-mediated and antibody responses are different.